The innovativeness of Knowledge-Intensive Business Services in the context of market needs - Borodako, Krzysztof; Berbeka, Jadwiga (Innowacyjność dostawców usług biznesowych opartych na wiedzy w kontekście potrzeb rynkowych, 2019)
The issue of innovativeness is gaining importance due to rapid changes that enterprises have to face. The aim of this paper is to check if there is a relationship between the innovation level of Knowledge-Intensive Business Services (KIBS) providers and the level of visibility of a given type of business activity on the Internet. In the theoretical part, a review of Polish and English literature devoted to the issue of innovation measures, KIBS and the problem of visibility on the Internet was conducted. To implement the research objective, two research streams were integrated to examine the level of KIBS innovativeness – Statistics Poland data on the number of innovations implemented by individual KIBS suppliers with the results of a netnographic analysis presenting the level of visibility which can be considered as a determinant of the level of relative demand for given services. The results of the analysis show the level of innovation of individual KIBS and point to the weak relationship with the level of visibility on the Internet
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 187-202
Keywords: innovation; knowledge-intensive business services; SEO; visibility; innowacje; usługi biznesowe oparte na wiedzy; widoczność w internecie